The Effects of Nutrition on the Health and Development of the Fetus in Pregnant Women - Utami; Yolanda Lusia Sepang, Mareyke; Sri Aisyah Hidayati; Deddy S. Razak; Nelwetis (CV. Get Press Indonesia, 2024)
Proper nutrition during pregnancy plays a crucial role in supporting fetal development and maintaining the mother's health. However, there is still a knowledge gap among pregnant women, especially in rural and remote areas, regarding the importance of nutritional intake during pregnancy. This study is aimed at comprehensively analyzing the impact of maternal nutritional intake on maternal health and growth. Methods. The study involves 150 purposively selected pregnant women who visited Puskesmas, health clinics, or maternal and child hospitals in Padang City during the 6-month period of the study. The data collection technique is done by interviewing pregnant women using questionnaires related to demographics and diet. The collected data will be analysed using statistical methods, descriptive test to see the general description of the characteristics of pregnant women and their nutritional intake, and chi square test to analyse the relationship between nutritional intake and infant birth weight (LBW). Results. Most pregnant women had a moderate level of knowledge about nutrition (46.7%), but there were 40% who had low knowledge. There was a significant relationship between pregnant women's knowledge level about nutrition and nutrient intake and its impact on LBW. Conclusions. Pregnant women have a low knowledge level regarding nutrition, which in turn affects foetal health, growth, and quality of life. With these measures, it is hoped that the risk of pregnancy complications due to malnutrition can be minimised and the quality of maternal and infant health can be significantly improved.